Sacituzumab Govitecan for the treatment of advanced triple negative breast cancer patients: a multi-center real-world analysis - Caputo, Roberta; Buono, Giuseppe; Piezzo, Michela; Martinelli, Claudia; Cianniello, Daniela; Rizzo, Alessandro; Pantano, Francesco; Staropoli, Nicoletta; Cangiano, Rodolfo; Turano, Salvatore; Paris, Ida; Nuzzo, Francesco; et al. (Frontiers in Oncology, 2024)
Objective. The objective of this multicenter, observational, retrospective analysis was to evaluate the safety and efficacy of sacituzumab govitecan in metastatic triple-negative breast cancer (mTNBC) patients managed according to common clinical practice in Italy.Methods. Data were retrieved by 7 sites. Triple-negative BC was defined by the lack of expression of estrogen receptor (ER <1%), progesterone receptor (PgR <1%) and human-epidermal growth factor receptor-2 (HER2 0, 1+, 2+ ISH-not amplified) according to standard ASCO-CAP criteria.Demographic and clinical characteristics were collected. Premedication, dose modifications and treatment schedule were based on the approved label of the product. Adverse events (AEs) were assessed according to NCI-CTCAE v5.0.Results. Fifty-seven eligible patients who received sacituzumab govitecan for mTNBC were included. Median age was 53 years (range 25-75). Approximately 70% of patients had an initial diagnosis of TNBC. Median time from the diagnosis of metastatic BC to start of sacituzumab govitecan was 17 months (range 0-97) and median number of previous therapies was 3 (range 1-7).The most common sites of metastasis were lymph nodes (63.1% of patients), lung (57.9%), bone (50.8%) and liver (38.6%). Eight (14.0%) patients had a disease-free interval ≤12 months. A total of 32 (56.1%) deaths were observed and the median overall survival (OS) was 12.43 months (95% CI, 7.97 months-not reached). At a median follow-up of 10.6 months, 45 patients (78.9%) had progression and the median progression-free survival (PFS) was 4.9 months (95% CI, 3.7-7.1 months). Partial tumour response was observed in 19 patients (33.3%), stable disease in 16 (28.1%) and disease progression in 22 patients (38.6%). The most common treatment-related AEs were anemia (66.6% of patients), alopecia (66.6%), neutropenia (59.6%), nausea (42.1%) and diarrhea (38.6%). Neutropenia was the most common serious treatment-related AE: 21.0% and 8.7% of patients experienced grade 3 or 4 neutropenia, respectively. Twenty-two patients (38.6%) reduced the dose and 5.3% permanently discontinued treatment.The results of this real-world analysis showed that both safety and efficacy of sacituzumab govitecan in mTNBC patients are consistent with that previously reported in regulatory trials. The use of premedication and supportive measures was associated with a satisfactory toxicity profile.